Psychosocial impact of novel COVID-19 on dental professionals - Current analysis and scoping review - Srinandan Pradhan; Prerna Upadhyay; Disha Gupta; Swapna Chavan; Parveen Kumar; Nirma Yadav (Wolters Kluwer Medknow Publications, 2020)
The human civilization of the world is probably going through the most important turning point of this millennium, in which the existence of humans is being challenged by the emergence of a severe respiratory syndrome novel coronavirus-19 (nCov-19), which can be seen in new areas around the world attempting to encroach and destroy. nCoV-19 pandemic has created a challenge for scientists and doctors from worldwide how to treat infected patients while protecting themselves from this infection, and the significant effect of this pandemic is on treating eye and dental diseases. The novel coronavirus disease 2019 (nCOVID-19) transmission through contact with droplets and aerosols generated during dental clinical procedures is expected. Hence, especially for dentists and health-care professionals that perform aerosol-generating procedures are restricted. As a result, severe financial implications being faced by dentists and health-care workers. Like other pandemics and emerging disease outbreaks, nCOVID-19 is creating immense psychosocial disturbances. The collective fear of nCOVID-19, which can be felt among working dental professionals in institutions, may be called "Dento-Coronophobia," has led to an excess of psychotherapeutic manifestations at various levels of society. Therefore, this review has been done to define the psychological effect of nCOVID-19 on dental practitioners.